Pengaruh Keaktifan di Organisasi dan IPK terhadap Softskills dan Kesiapan Menjadi Guru Mahasiswa Pendidikan Teknik Otomotif - Ibnu Siswanto; Ika Wahyu Noor Arifah; Febryan Edwin Nur Ramadhan (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstracts. Organizations teaching softskills and hardskills are useful for social life, but organizations are not being priority for students. Therefore, this study aims to find out whether the organization can influence the readiness to become teachers and softskills from the students of FT UNY. In addition, this study looks for whether the GPA that is used as an orientation by students also influences the readiness to become a teacher and student softskill. In this study, data was collected using a questionnaire with a sample of 116 students. This study has six hypotheses that have been tested using simple regression and multiple regression, all of which show ha is accepted and h0 is rejected, namely that there is a positive influence between activeness in the organization and readiness to become a teacher. There is a positive influence between activeness in the organization of softskills. There is a positive influence between GPA and readiness to become a teacher. There is a positive influence between GPA and softskills. There is a positive influence between activeness in the organization and the GPA jointly towards readiness to be a teacher, and there is a positive influence between activeness in the organization and GPA together on softskills.